The Analysis of Leading Sectors in Nagan Raya Regency, 2019–2024 - Efendi, Jeltaria; Yasrizal, Yasrizal; Risma , Okta Rabiana (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze the specialization of economic sectors in Nagan Raya Regency using the Location Quotient (LQ) method and to examine its correlation with regional economic growth. The LQ method is employed to identify leading (basic) sectors that possess higher comparative competitiveness than those at the regional or national level. Furthermore, the study analyzes how the development of these basic sectors contributes to the Gross Regional Domestic Product (GRDP) and other economic growth indicators in Nagan Raya Regency. Based on the Location Quotient analysis, the results for 2024 indicate that there are three sectors categorized as basic or leading sectors, namely the mining and quarrying sector, the agriculture, forestry, and fisheries sector, and the other services sector. The remaining sectors are classified as non-basic or non-leading local sectors because their LQ values are below 1. These sectors include: (1) manufacturing industry; (2) electricity and gas supply; (3) water supply, waste management, and recycling; (4) construction; (5) wholesale and retail trade, and repair of motor vehicles and motorcycles; (6) transportation and warehousing; (7) accommodation and food service activities; (8) information and communication; (9) financial and insurance services; (10) real estate; (11) business services; (12) public administration, defense, and social security; (13) education services; and (14) health and social services.